Development and Feasibility of Environmental Knowledge Test Instruments With Low Carbon Education Content for Prospective Science Teachers - Muhammad Syahruddin Amin (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This study aims to develop and measure the feasibility of an environmental knowledge test with low-carbon education content for prospective science teachers. This study is R&D using the ADDIE model. The content validity of the test was measured on three aspects by five experts, and the content validity coefficient of each test item was calculated using Aiken's formula. The analysis shows that the environmental knowledge test with low carbon education content is classified as strongly valid in 3 aspects with scores of 93.2% (aspect #1), 93.4% (aspect #2), and 94.4% (aspect #3) each. Analysis using Aiken's V also shows that all items of the environmental knowledge test with low carbon education content are in the high category with an average index of 0.92. This study concludes that ecological knowledge tests with low-carbon education content can be developed and are feasible for prospective science teachers to use. As the first environmental literacy test with LCE content, the results of this study provide a new base and reference for research, further development, or application of ecological literacy tests with LCE content.